Performance-Oriented Parametric Design Method for Early-Stage Residential Design in Northern China - Zhang, Jingyu (Journal of Progress in Civil Engineering, 2025)
This paper proposes a performance-oriented parametric design method for early-stage residential design in Northern China, addressing the critical need for residence energy efficiency in cold climates. By integrating energy simulation goals with parametric design techniques, this study develops a framework that leverages digital tools and artificial intelligence to optimize residential schemes. The methodology emphasizes data-driven design processes, enabling architects to explore multiple design possibilities while ensuring alignment with energy-saving targets. The paper outlines the theoretical foundations, workflow, and validation of the proposed methodology through case studies, demonstrating its potential to enhance energy performance in residential architecture.